2023
DOI: 10.1108/bl-04-2021-0058
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health information acceptance to COVID-19 avoidance: the lens of information acceptance model and elaboration likelihood model

Abstract: Purpose This study aims to analyze the motivations underlying information usefulness, attitude and acceptance of health information related to coronavirus disease 2019 (COVID-19) avoidance based on the information acceptance model (IAM) and the elaboration likelihood model (ELM). Design/methodology/approach This study conducted a quantitative approach using survey that generated 364 valid responses. Structural equation modeling was applied to analyze the data and evaluate the hypotheses. Findings The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
2
0
1
Order By: Relevance
“…ICTs drive competitiveness because of their efficiency in cost reduction and productivity (Valeri and Baggio, 2022;Cimbaljevi c et al, 2018). The advent of ICTs like mobile applications has accelerated the speed at which information proliferates (Ozor and Toner, 2022;Le, 2023). Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…ICTs drive competitiveness because of their efficiency in cost reduction and productivity (Valeri and Baggio, 2022;Cimbaljevi c et al, 2018). The advent of ICTs like mobile applications has accelerated the speed at which information proliferates (Ozor and Toner, 2022;Le, 2023). Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…Nonetheless, if chatbots convey information not closely associated with customer interests, customers perceive these chatbots as less useful. Therefore, marketers should pay special attention to the reasons behind perceived usefulness through information credibility and attitude toward AI (Le, 2023). When AI is still in the embryonic stage, marketers should promote its advantages and applications to potential users (e.g.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…ELM đã được áp dụng vào bối cảnh thông tin trong COVID-19 (Le, 2023a), truyền thông xã hội (Le, 2021), mua sắm trực tuyến (Thomas và cộng sự, 2019), giới thiệu trực tuyến (Luo và cộng sự, 2013). Le (2023a) 2019) phân tích dự định mua sắm thông qua hướng trung tâm (sự chính xác, tính đầy đủ, tính kịp thời) và hướng ngoại vi (số lượng, tính đồng nhất và chuyên môn đánh giá) của đánh giá trực tuyến. Le (2022) chỉ ra hướng trung tâm (chất lượng thông tin) và hướng ngoại vi (nhận thức rủi ro) tác động đến ý định mua sắm.…”
Section: Thuyết Khả Năng Xây Dựng Thuyết Phụcunclassified